Extragastrointestinal Stromal Tumor during Pregnacy. (18th October 2012) - Gözükara, Ilay; Dilek, T. U. Kutlu; Durukan, Hüseyin; Düsmez Apa, Duygu; Kabil Kucur, Suna; Dilek, Saffet
Abstract : Extragastrointestinal stromal tumors (EGISTs) are mesenchymal neoplasms without connection to the gastrointestinal tract. Gastrointestinal stromal tumors (GISTs) and EGIST are similar according to their clinicopathologic and histomorphologic features. Both of them most often express immunoreactivity for CD-117, a c-kit proto-oncogene protein. The coexistence of GIST and pregnancy is very rare, with only two cases reported in the literature. In this paper, we presented the first EGIST case during pregnancy in the literature.